Stocking density effect on growth homogeneity of juvenile pirarucu in confined environments - Cavero, Bruno Adan Sagratzki; Filho, Manoel Pereira; Roubach, Rodrigo; Ituassú, Daniel Rabello; Gandra, André Lima; Crescêncio, Roger (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the stocking density over fish growth homogeneity of pirarucu (Arapaima gigas) juveniles in small volumes cages. Twelve 1 m3 net-cages were used in a 120 m2 earth pond consisting of three treatments (15, 20 and 25 fish/m3) with four repetitions each. Fish were stocked with an initial mean weight of 10.1±0.3 g and homogeneous distributed (p > 0.05) between treatments. Coefficient of variation for growth and condition factor did not present significant (p > 0.05) differences, contrary to consumption and apparent feed conversion (p < 0.05). Consumption was inversely proportional to the increment of density, indicating that stockings densities increases are favorable to a better feed use. There were not any observed behavior differences between treatments. Juveniles pirarucu growth was not influenced by the stocking density or intra-specifics interactions.